LeanWOOD – towards resilient design and building processes. (August 2019) - Geier, S
Abstract: With the introduction of the concept of resilience in the discourse of building design, design and building processes have to react to complex challenges presented by the extension of the perspective from physical building structure to living space. Instead of conserving effort, resilience demands integrated and argumentative processes and interdisciplinary cooperation. Forerunners in industrialized timber construction have long-standing experience and are starting points for new advanced design processes. The international leanWOOD project (2014-2017) aimed at outlining the requirements for future timber building planning processes to put them on a broader base and thus contribute to advanced processes in the future. To achieve resilience in building design, rigid and sequential process-chains must turn into flexible, argumentative process approaches. The paper illustrates the key elements for resilience-oriented design processes, discusses procurement and cooperation models, identifies pitfalls in current development and outlines the impact on resilient buildings. Finally, the outlook shows the potential of the implementation of BIM to this change towards resilient design and building processes.